Microstructural performance of quartz-based pre-filtration devices for oil/water separation - Ramanamane, Nthabiseng; Pita, Mothibeli (International Journal of Innovative Research and Scientific Studies, 2025)
Effective and affordable technologies are urgently needed for oily wastewater treatment, where conventional polymeric membranes suffer from fouling and ceramic membranes remain cost-prohibitive. This study investigates quartz particles (0.8–1.8 mm) as a low-cost pre-filtration medium for oil/water separation, focusing on the influence of raw versus acid-washed surfaces. Experiments using a packed quartz bed demonstrated that both media substantially reduced influent oil concentrations (initial 4393.80 mg/L), with raw quartz achieving 98.07% removal and washed quartz further improving efficiency to 98.48%. Surface cleaning enhanced quartz performance by eliminating impurities, increasing effective porosity, and restoring natural hydrophilicity, thereby improving adsorption and minimizing pore blockage. These findings highlight washed quartz as a structurally robust, scalable, and environmentally sustainable medium that can serve as a first-line barrier in multi-stage oily wastewater treatment systems. The slight yet meaningful efficiency gain with washed quartz demonstrates its industrial relevance, as even marginal improvements translate into significant operational benefits at scale. Overall, quartz offers a practical, low-cost alternative to conventional filtration materials, reducing the treatment burden on downstream polishing units and supporting water reuse in oil-intensive industries.